HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN KINERJA GURU DI SMK SWASTA BISNIS MANAJEMEN KECAMATAN PADANG BARAT KOTA PADANG - WINDA SRI ASTUTI (Jurnal Bahana Manajemen Pendidikan, 2018)
The purpose of this research is for getting information about school climate, spirit at work and the correlation of school climate with the spirit at work. The background of this research that the spirit at work is influenced by the school climate. The population of this research is a vocational school teachers, amounting to 124 with a total sample of 97 people by using proportional stratified random sampling technique. The research instrument used was a questionnare. In general, the result research adduce that the school climate was good with interpretation 89,44%, school climate was good enough with interpretation 88,85% and there was a significant correlation between school climate with the spirit at work at t hitung = 2,66 > t tabel = 1,658 pada taraf kepercayaan 95%.